2021
DOI: 10.3390/land10020092
|View full text |Cite
|
Sign up to set email alerts
|

Which Traits Influence Bird Survival in the City? A Review

Abstract: Urbanization poses a major threat to biodiversity worldwide. We focused on birds as a well-studied taxon of interest, in order to review literature on traits that influence responses to urbanization. We review 226 papers that were published between 1979 and 2020, and aggregate information on five major groups of traits that have been widely studied: ecological traits, life history, physiology, behavior and genetic traits. Some robust findings on trait changes in individual species as well as bird communities e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 189 publications
(307 reference statements)
0
23
0
Order By: Relevance
“…Urban areas are growing exponentially, leading more wildlife species to reside in urban environments as their alternative habitats. Mounting evidence has shown that urban environments have changed wildlife’s fitness-related traits ranging from physiology (2) to morphology (3, 4), and not least behaviour (510). As of yet, investigations are still in infancy regarding how urban environments shape cognition (11, 12), a crucial fitness-related trait that can be considered as the process of acquiring, storing, utilising and reacting to their environment (13).…”
Section: Introductionmentioning
confidence: 99%
“…Urban areas are growing exponentially, leading more wildlife species to reside in urban environments as their alternative habitats. Mounting evidence has shown that urban environments have changed wildlife’s fitness-related traits ranging from physiology (2) to morphology (3, 4), and not least behaviour (510). As of yet, investigations are still in infancy regarding how urban environments shape cognition (11, 12), a crucial fitness-related trait that can be considered as the process of acquiring, storing, utilising and reacting to their environment (13).…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Predatory pressure and food resources are two main factors that profoundly influence the ecology and evolution of avian reproduction. 16,17 Those selective pressures always vary in different populations, especially, compared with rural populations, urban populations have different predator composition and alternative food sources for predators. 18 Meanwhile, interspecific brood parasitism rate increases with distance from the nearest human habitation.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing human population is dominated on the ecosystems, intensifying human land use and thus affecting the biodiversity (Foley, 2005;Patankar, 2021). Effects of these activities are manifested at all ecological scales, through local extirpations and global extinctions (Pimm et al, 1995;Chapin et al, 2000).…”
Section: Introductionmentioning
confidence: 99%